2018
DOI: 10.1186/s12873-018-0196-z
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic guided hydrostatic saline enema reduction of childhood intussusception: a prospective study

Abstract: BackgroundThe management of childhood intussusception in our sub-region is still via surgical intervention. Currently, the gold standard of treatment is non-operative reduction. We sought to assess the suitability of hydrostatic (saline) reduction of intussusception in children in our institution.Materials and methodsA prospective study was conducted between January 2016 and June 2017 in all children with ultrasound confirmed intussusception at a tertiary teaching hospital in Nigeria. All children excluding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 27 publications
4
54
0
Order By: Relevance
“…In the present study, ileocolic (idiopathic) type of intussusception was the most common type. This is consistent with the observation of most series [ 7 , 14 , 23 ]. Other types of intussusception such as ileoileal, colocolic, jejunoileal, jejunojejunal can also occur in children but they are far less common than ileocolic type.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In the present study, ileocolic (idiopathic) type of intussusception was the most common type. This is consistent with the observation of most series [ 7 , 14 , 23 ]. Other types of intussusception such as ileoileal, colocolic, jejunoileal, jejunojejunal can also occur in children but they are far less common than ileocolic type.…”
Section: Discussionsupporting
confidence: 94%
“…It is noteworthy that this late presentation is mostly seen in developing countries where there is lots of poverty and ignorance. The finding of abdominal pain as the most common presenting symptom of intussusception is in line with the reports of other studies [ 14 , 18 ]. However, other studies reported vomiting and abdominal mass as the most common symptoms [ 4 , 15 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, the confirmed diagnosis is mainly based on ultrasound findings, and a pediatric surgeon should decide whether to take the infant for an enema pneumatic reduction or close surveillance [10][11]. Besides, choosing an intervention between saline-enema and pneumatic reduction for the treatment of acute intussusception is under debate due to the varied success rate of 83%-88% [12][13][14][15]. This prospective study aims to describe the clinical manifestation and develop a conservative management protocol for acute ileocaecal intussusception in children under two years of age.…”
Section: Introductionmentioning
confidence: 99%